Learning History Through LENS: Critical Analysis of Narratives in Documentary Films - Gedhe Ashari; Ari Sapto; Inda Wahyu Puji Utami (South Sulawesi Education Development (SSED), 2025)
History learning in the digital era faces challenges in attracting interest and building students' critical understanding of past events. One innovative approach that can be used is the use of documentary films as a learning medium. Documentaries are not only informative, but also present a narrative that is reflective of historical constructions. This study aims to analyze the use of documentary films in history learning and develop critical analysis strategies through the Learning History through the Exploration of Narratives on Screen (LENS) model. This study uses the Dick and Carey instructional design method which consists of ten systematic steps, namely: identification of learning objectives, analysis of learning and student characteristics, formulation of special learning objectives, development of evaluation instruments, development of learning strategies, development and selection of materials, development of learning media, implementation of learning, and formative and summative evaluation. Historical documentaries are used as the primary source in analytical activities to train students' interpretive, analytical, and reflective abilities against visually presented historical narratives. The results of the study show that the integration of documentary film into history learning through the LENS strategy is able to improve students' active participation, critical thinking skills, and historical awareness. This strategy also encourages students to question dominant narratives, evaluate different perspectives, and develop media and historical literacy in an integrated manner. Thus, this approach can be an effective alternative in creating more contextual, interactive, and meaningful history learning.